Compulsory Arbitration in New Zealand The First Forty Years. - Holt, James (Auckland University Press, 2013)
This book traces the history of one of New Zealand's most famous laws, the Industrial Conciliation and Arbitration Act of 1894. Holt explains how the law was enacted and how it was transformed by judges over the next forty years into something which had not been envisaged by W. P. Reeves and his fellow legislators. By not only resolving labour disputes but also fixing minimum wages, maximum hours and conditions of employment, the court achieved a pivotal influence on New Zealand economic, social and political life.